Gender bias in social services? An analysis using focused ethnography - Lucas-García, Jezabel; Bayón-Calvo, Siro; Gómez-García, Rogelio (Cuadernos de Trabajo Social, 2022)
Are women discriminated when seeking social services? Using a focused ethnography, this paper addresses this question by analysing how users of social services face gender biases, and describing how social workers assimilate and reproduce these constructs. As familiarism is a defining feature of the Mediterranean welfare states, gender biases are likely to appear, evidenced in the direct interventions with social workers. We focus on the case of a centre of general social services located in Basque Country, analyzing 57 cases of vulnerable men and women, paying attention to the social interventions they receive. The study period coincides with a scenario of economic downturn in which austerity-based policies have played a leading role. The results evidence an absence of a gender perspective in a system that has not been sufficiently transformed to achieve gender equity. Gender bias is evidenced in social intervention in a significant number of the cases, as social worker actions reproduce the perpetuation of a sexual division of labour and do not promote mechanisms of co-responsibility.
Keywords: Gender bias; Social services; Focused Ethnography; Basque Country; Social intervention